Addition of molybdate ions to the anodizing bath to improve the corrosion resistance of clad 2024-T3 alloy anodized in tartaric-sulfuric acid - Almeida, Thassia Felix de; Prada Ramirez, Oscar Mauricio; Lanzutti, Alex; Rodrigues, Cleber Lima; Brabetz, Manfred; Kremmer, Thomas M.; Hammer, Peter [UNESP]; de Melo, Hercilio Gomes (Elsevier, 2024)
In the present investigation molybdates ions (MoO4−2) were added to a tartaric‑sulfuric acid (TSA) bath, which was employed to anodize AA2024-T3 clad samples. The incorporation of Mo into the anodized layer was investigated by different techniques: X-ray photoelectron spectroscopy (XPS), glow-discharge optical emission spectroscopy (GDOES), Rutherford backscattering spectrometry (RBS) and scanning electron microscopy (SEM), while the corrosion resistance was evaluated by electrochemical impedance spectroscopy (EIS) techniques in neutral (0.5 M) and acidic (0.1 M, pH = 4.0) NaCl solutions. The different characterization techniques indicate that small amounts of the modifier were incorporated into the anodized layer, while the SEM analysis confirmed that the morphology of the layer was not changed, although it was thicker when anodized in the Mo containing bath. Evaluation of corrosion resistance by EIS in both media showed that samples anodized in the molybdate containing bath were more corrosion resistant and durable. Fitting results of the electric equivalent circuit indicate that this may be a consequence of a thicker barrier layer for these samples.
Keywords: 2024-T3 clad; EIS; Modified anodizing bath; Sodium molybdate; Tartaric‑sulfuric acid